Information needs, preferred educational messages and channel of delivery, and opinion on strategies to promote organ donation: a multicultural perspective - Wong, Li Ping (Singapore Medical Association, 2010)
INTRODUCTION: This study assessed the information needs, preferred educational messages and channels of delivery, as well as opinions on strategies to promote organ donation. It aimed to provide insight into a culturally sensitive public education campaign to encourage organ donation in diverse ethnic communities in Asia, namely the Malays, Chinese and Indians.